STRATEGI PENGEMBANGAN MATERI PAI BERBASIS MODERASI BERAGAMA DI ERA DIGITAL - Prihatin, Nyimas Yunierti; Irawan, Dodi; Agustina, Rika Hasmayanti (Jurnal Manajemen Pendidikan, 2025)
The rapid development of digital technology has fundamentally transformed the patterns of religious authority and communication, including within Islamic Religious Education (PAI). This phenomenon presents serious challenges, such as the weakening of teachers' authority, the spread of intolerant Islamic content online, and the digital literacy gap between educators and learners. This study aims to formulate strategic approaches for developing PAI instructional materials based on religious moderation that are contextually relevant, inclusive, and responsive to the digital reality. Employing a qualitative descriptive approach through library research, this study analyzes scholarly literature, previous research findings, and official policy documents, particularly the Minister of Religious Affairs Decree No. 347 of 2022 concerning the implementation of the Merdeka Curriculum in madrasahs. Data were analyzed using content and thematic analysis techniques to identify core concepts and strategies for integrating moderation values into PAI materials. The findings reveal that effective strategies include: (1) integrating moderation values into learning outcomes and curriculum design, (2) developing educational, contextual, and narrative-based digital content, (3) enhancing PAI teachers’ digital literacy and critical pedagogy competencies, and (4) strengthening intersectoral collaboration between schools, government, and digital communities. With these strategies, PAI can function not only as a vehicle for religious instruction but also as a transformative educational space that cultivates moderate, critical, and socially engaged religious character in the digital era.